A study of metal-MoS2 contacts by using an in-house developed ab-initio transport simulator. (August 2022) - Lizzit, Daniel; Khakbaz, Pedram; Driussi, Francesco; Pala, Marco; Esseni, David
Highlights: An efficient ab initio simulator has been used to investigate the transport properties of metal-TMD contacts. Insulating buffers with atomic thickness can mitigate the metal-TMD Schottky Barrier. Graphene buffer layers are not always effective in reducing the metal-TMD Schottky Barrier. Abstract: By combining DFT calculations and an in-house developed, ab - initio transport simulator, we investigate the transport properties of n -type contacts between 3D metallic conductors and monolayer MoS2 . Moreover, the impact of buffer layers between the metal and the MoS2 is also analyzed in order to reduce the Schottky barrier and approach the Ohmic behavior of contacts.